2021
DOI: 10.1186/s12872-021-02063-w
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic microvascular complications are associated with reduced global longitudinal strain independent of atherosclerotic coronary artery disease in asymptomatic patients with diabetes mellitus: a cross-sectional study

Abstract: Background Reduced left ventricular function, assessed by global longitudinal strain (GLS), is sometimes observed in asymptomatic patients with diabetes mellitus (DM) and is often present in patients with diabetes-related microvascular complications. Our aim was to assess the association between microvascular complications, coronary artery plaque burden (PB) and GLS in asymptomatic patients with DM and non-obstructive coronary artery disease (CAD). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…A cross‐sectional study including 82 T2DM patients demonstrated that GLS was free from the impacts of retinopathy 29 . Similarly, Pararajasingam et al also pointed out that none of the subgroups of retinopathies had a relation to GLS 30 . However, increasing studies demonstrated the prominent relation of the diabetic retinopathy to the impaired LV systolic function as evaluated by GLS <18% 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study including 82 T2DM patients demonstrated that GLS was free from the impacts of retinopathy 29 . Similarly, Pararajasingam et al also pointed out that none of the subgroups of retinopathies had a relation to GLS 30 . However, increasing studies demonstrated the prominent relation of the diabetic retinopathy to the impaired LV systolic function as evaluated by GLS <18% 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Data for the current study was derived from a previous prospective observational single-center study performed at Odense University Hospital, Svendborg, Denmark, from March 2016 to September 2018 [32,33]. The primary aim of the original study was to investigate the changes in plaque burden and composition in T2DM.…”
Section: Methodsmentioning
confidence: 99%
“…It is now included in routine evaluation, especially for patients who receive cardiotoxic chemotherapy 6 . GLS was also found to be associated with cardiovascular events in DM patients who do not have a history of cardiovascular complications 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 GLS was also found to be associated with cardiovascular events in DM patients who do not have a history of cardiovascular complications. 7 The myocardial mechano-energetic efficiency (MME) method has been used in recent years to provide important information on the structure, functions, and oxygen consumption of the myocardium. It has come to the forefront as an effective method in predicting preclinical cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%